Trans self-identification and the language of neoliberal selfhood: Agency, power, and the limits of monologic discourse - Zimman, Lal (International Journal of the Sociology of Language, 2019)
Sociocultural linguists share with transgender communities a strong interest in the power of individuals to assert agency over linguistic patterns. For trans people, a key principle of activism is gender self-determination, which treats each individual as the ultimate authority on their own gender identity. This article explores some of the ways gender self-determination and self-identification surface in transgender people’s linguistic practices. Three particular manifestations are highlighted: gendered identity labels, third person pronouns, and body part terminology. The observations offered on these subjects are based on a series of ethnographic projects carried out from 2006–2016 in transgender communities across several metropolitan areas in the United States and in online spaces frequented by trans people. However, the analysis goes beyond mere description by treating this kind of individualized linguistic agency as the product of cultural practice rather than an asocial given. Such a perspective introduces questions concerning why this form of agency arose in the time and place that it has. This article frames gender self-identification as an enactment of neoliberal personhood, in which individuals are framed as the driver of their destiny. What the ideology of neoliberal agency obscures, however, is that agency is not an equally distributed resource.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; LGBTQIA2+; agentivité; amériques; approches et analyses; cours; discipline; identités LGBTQIA2+; lin2685; linguistique; néolibéralisme; premier cycle; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sofia; thématiques; transféminisme; états-unis

Queer excursions: retheorizing binaries in language, gender, and sexuality - Zimman, Lal; Davis, Jenny L.; Raclaw, Joshua (Oxford University Press, 2014)
Across scholarship on gender and sexuality, binaries like female versus male and gay versus straight have been problematized as symbols of the stigmatization and erasure of non-normative subjects and practices. The chapters of Queer Excursions offer a series of distinct perspectives on these binaries as well as on a number of other, less immediately apparent dichotomies that nevertheless permeate the gendered and sexual lives of speakers in various contexts. Some chapters focus on the limiting or misleading qualities of binaristic analyses, while others suggest that binaries are a crucial component of social meaning within particular communities of study. Rather than simply accepting binary structures as inevitable, or discarding them from our analyses entirely based on their oppressive or reductionary qualities, this volume advocates for a retheorization of the binary that affords more complex and contextually grounded engagement with speakers’ own orientations to dichotomous systems. It is from this perspective that contributors identify a number of diverging conceptualizations of binaries—including those that are non-mutually exclusive, those that liberate in the same moment that they constrain, those that are imposed implicitly by researchers, and those that recontextualize familiar divisions with innovative meanings. With each chapter having a perspective on locally salient linguistic practices that help constitute gender and sexuality in marginalized communities, what the contributions to Queer Excursions together demonstrate is that researchers must be careful to avoid the assumption that our own preconceptions about binary social structures will be shared by the communities we study.
Donné en lecture au cours LIN2685 et POL4105, Jenny L. Davis, “More Than Just ‘Gay Indians’”: Intersecting Articulations of Two-Spirit Gender, Sexuality, and Indigenousness, pp62-80.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; identités LGBTQIA2+; langage; lin2685; linguistique; pol4105; premier cycle; queer; ressource en ligne; sciences humaines; sociolinguistique; sofia; thématiques